2022
DOI: 10.1016/j.euros.2021.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Primary Renal Tumour Response in Patients Treated with Nivolumab and Ipilimumab for Metastatic Renal Cell Carcinoma: Real-world Data Assessment

Abstract: Following CARMENA and SURTIME, patients with metastatic renal cell carcinoma (mRCC) and International Metastatic RCC Database Consortium (IMDC) intermediate and poor risk receive systemic therapy with the primary tumour (primary) in place, with the option of deferred cytoreductive nephrectomy (CN) in responding patients. We retrospectively analysed the safety and efficacy of first-line nivolumab/ipilimumab in 71 primary mRCC patients (42.3% IMDC poor risk; 43.6% with more than three metastatic sites). The base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…From this point of view, it seems more convenient to start with systemic therapy to achieve disease control; on the other hand, the window of opportunity for removing the primary tumor can be missed irreversibly. Interestingly, a retrospective analysis of 71 mRCC patients treated with ipilimumab and nivolumab upfront with the option of deferred CN in responding patients showed a 33.3 % response rate in the primary site and a 91.3% overall response rate at metastatic sites regardless of the prognostic group [ 45 ]. CN was performed in 18.8% of the patients after a median time of 13 months [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this point of view, it seems more convenient to start with systemic therapy to achieve disease control; on the other hand, the window of opportunity for removing the primary tumor can be missed irreversibly. Interestingly, a retrospective analysis of 71 mRCC patients treated with ipilimumab and nivolumab upfront with the option of deferred CN in responding patients showed a 33.3 % response rate in the primary site and a 91.3% overall response rate at metastatic sites regardless of the prognostic group [ 45 ]. CN was performed in 18.8% of the patients after a median time of 13 months [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a retrospective analysis of 71 mRCC patients treated with ipilimumab and nivolumab upfront with the option of deferred CN in responding patients showed a 33.3 % response rate in the primary site and a 91.3% overall response rate at metastatic sites regardless of the prognostic group [ 45 ]. CN was performed in 18.8% of the patients after a median time of 13 months [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the assumption that the overall indication for deferred CN may therefore increase, overall response rates to systemic therapy range from 46% to 60%, with complete responses occurring in only one in every ten patients [6] . Real-world data for patients treated with nivolumab and ipilimumab with the primary tumour in place revealed that only 13% were offered deferred CN [7] . Thus, cytoreductive surgery for the primary tumour as a procedure, whether upfront or deferred, has become a rare intervention for which to select candidates for PN.…”
mentioning
confidence: 99%
“…An additional argument against PN in the metastatic setting is the complexity of primary tumours. In metastatic disease, primary tumours are 9 cm in diameter on average [2] , [3] and although downsizing can be expected on ICI combination therapy [7] , [8] , a reduction in primary tumour diameter of ≥30% occurs in only one-third of patients [8] . According to real-world data for patients in the intermediate IMDC group treated with dual ICI and the primary tumour in place, the baseline median primary tumour size was 14 cm, which decreased by a median of only 12.9% [7] .…”
mentioning
confidence: 99%
See 1 more Smart Citation